Experimental analysis on passive bandwidth estimation tools for iperf, netperf and spruce for mesh wireless local area network (WLAN) - Nurul Izwani, Norhan (2014)
Available bandwidth estimation is useful for route selection in a network environment. While many tools has been created to estimate the available bandwidth, mainly by two techniques passive and active measurement. Passive measurement is performed by observing the traffic without intruding the network. Active measurement on the other hand, will probe the network by generating packet traffic into the network to perform the measurement with the availability of multiple available bandwidth estimation tools around, the question is which bandwidth estimation tool will be the best to perform the task in a given network situation? Which tools perform the best when fluctuation of bandwidth happens in a network? Accurate estimating available bandwidths in a network path are important for the right and efficient operation of many Internet applications and protocols as well as network management applications. End-to-end flow control, server selection for downloads and streaming media, peer-to-peer web host selection and content delivery, and multicast configuration protocols are just a few examples where accurate bandwidth estimations are valuable. This research will represent an experimental analysis of available bandwidth by using a few bandwidth estimation tools which are Iperf, Netperf, Spruce. The objective of the research is to measure available bandwidth with selected bandwidth estimation tools, compare the selected tools based on their estimation preference and to recommend the best bandwidth estimation tools in the three factors which are the failure pattern, accuracy and consistency of the tools.